PENGEMBANGAN MODEL PEMBELAJARAN MENULIS TEKS PROSEDUR BERBANTUAN MEDIA BOOK CREATOR - Fibri Ledia Alviana; Alif Mudiono; Muh. Arafik (JDMP (Jurnal Dinamika Manajemen Pendidikan), 2024)
Writing skills in Indonesian language lessons are often considered more challenging to master than other language skills. This study aims to develop a procedural text writing model for fourth-grade students based on the Genre Pedagogy approach and supported by Book Creator as a digital learning medium. The research employs a design-based research (DBR) method through stages of analysis, design, development, and evaluation. The instructional model integrates Genre Pedagogy steps—building knowledge, modeling, joint construction, and independent writing—into each learning activity. Book Creator is used to provide interactive content, including images and videos, to enhance student engagement. Results indicate that the developed model effectively supports students in writing procedural texts with clear structure, accurate information, and varied sentence patterns. The integration of digital media also increases student motivation and participation in writing activities. This study concludes that the Genre Pedagogy-based model with Book Creator media can improve writing skills in procedural texts among elementary students.